Zapata Retold: Attorneys’ Fees Are (Still) Not Governed by the CISG - Lookofsky, Joseph; Flechtner, Harry (Journal of Law and Commerce, 2008)
In Viva Zapata (the 1952 movie), a Mexican revolutionary hero named Zapata led a band of hungry peasants in a wild uprising against the government in power. In the film, Zapata (played by Marlon Brando, himself) scored some crowd-pleasing victories, but (historians tell us) the rule-making powers ultimately prevailed, reigning in the Wild One and ending (forever) Zapata’s quixotic quest.